Soil magnetic susceptibility analysis as an indicator of landslide-prone areas in Sanggau Regency, West Kalimantan Province, Indonesia - Muhardi; Perdhana, Radhitya (Journal of Degraded and Mining Lands Management, 2025)
Sanggau Regency is a highland area that has a rough topography with a relief of undulating hills, causing the potential for landslides. One of the steps to reduce the impact of landslides is to identify the characteristics of landslide-prone areas by conducting magnetic susceptibility analysis in landslide-prone areas. This analysis is a method to identify landslide indicators based on their magnetic properties. This method identifies landslide potential through superparamagnetic grains on the surface soil. The presence of the grain can be known from the frequency-dependent susceptibility . The study was conducted on 40 soil samples taken at a 20-30 cm depth at Jalan Sabang Merah, Sanggau Regency. The results showed that the average values of low-frequency  and high-frequency  were 5.555 cm3/g and 5.478 cm3/g, respectively. A total of 36 soil samples have a  percentage of 0% (containing less than 10% superparamagnetic grains), two soil samples have a  percentage of 3.51% and 6.45%, respectively (containing 10%-75% superparamagnetic grains, and two samples have a  percentage of 10.48%-12.63% (containing more than 75% superparamagnetic grains). The interpretation results show that soil samples with more than 75% superparamagnetic grains indicate landslide-prone areas in the study site; thus, the areas suspected to have a high level of vulnerability are in the northeastern and southwestern parts of the study site.